2017
DOI: 10.1590/s0100-736x2017000400007
|View full text |Cite
|
Sign up to set email alerts
|

Formação de biofilme por Vibrio parahaemolyticus isolados de pescados

Abstract: RESUMO: O pescado é um alimento altamente perecível, possui pH próximo a neutralidade, elevada atividade de água e alto teor de nutrientes facilmente utilizáveis por micro-organismos. Vibrio parahaemolyticus pode ser encontrado em ambientes com salinidade entre 3% e 8% e tem pH ideal para multiplicação entre 7,8 e 8,6. É um patógeno que pode causar gastrenterite aguda pelo consumo de frutos do mar contaminados, crus ou mal cozidos. Mesmo os processos de tratamento de água como cloração, adição de antibióticos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…The results obtained in the present study, like other studies that assessed the effect of sublethal stress on biofilm formation performed with different microorganisms (Rosa, et al, 2017;Galvão, et al, 2012;Lianou & Koutsoumanis, 2012), demonstrated that each microorganism, just as each strain of the same microorganism, has its own peculiarities when facing hostile environments, and may or may not form a biofilm.…”
Section: Resultssupporting
confidence: 81%
“…The results obtained in the present study, like other studies that assessed the effect of sublethal stress on biofilm formation performed with different microorganisms (Rosa, et al, 2017;Galvão, et al, 2012;Lianou & Koutsoumanis, 2012), demonstrated that each microorganism, just as each strain of the same microorganism, has its own peculiarities when facing hostile environments, and may or may not form a biofilm.…”
Section: Resultssupporting
confidence: 81%
“…Therefore, preventive approaches are needed, such as the control and monitoring of the microbiological quality of water, especially in high-risk food production environments (such as oysters, for example) and the microbiological control of these foods, including vibrio research. (Ramos et al, 2012) Oyster V. parahaemolyticus and V. vulnificus (ND) Florianópolis, SC (Ramos et al, 2014) Oyster V. parahaemolyticus (35%), V. vulnificus (10%), V. alginolyticus (7%) and V. fluvialis (2%) Mollusc farming water V. parahaemolyticus (45%), V. alginolyticus (29%) and V. vulnificus (13%) Florianópolis, SC (Silva et al, 2016a) Oyster and mussel V. parahaemolyticus (~ 11%) Shellfish farming water V. parahaemolyticus (18%) Lagoa dos Patos, RS (Rosa et al, 2016) Fish V. parahaemolyticus (<1%) Lagoa dos Patos, RS (Rosa et al, 2017) Fish V. parahaemolyticus (3.3%) Lagoa dos Patos, RS (Silveira et al, 2019) Fish Vibrio spp. (68%) and V. vulnificus (0.01%) Southeast region Rio de Janeiro, RJ (Oliva et al, 2016) Mussel V. parahaemolyticus (44.7%), V. alginolyticus (19.6%) and V. vulnificus (12.4%) Rio de Janeiro, RJ (Bouzas, 2021) Mussel V. parahaemolyticus (ND) Rio de Janeiro (Santos et al, 2021) Oyster farm V. parahaemolyticus (ND) Northeast region Baía de Todos os Santos, BA (Rodrigues & Carvalho, 2011) Oyster V. parahaemolyticus (ND)…”
Section: Discussionmentioning
confidence: 99%
“…Algumas espécies patogênicas de Vibrio têm sido relatadas na carcinicultura. Dentre estas, se destacam V. harveyi, que é uma bactéria Gram-negativa em forma de bastão que se locomove por meio de flagelos polares, ocorrendo especialmente em águas marinhas e salobras de clima quente da América do Sul, Ásia e sul da Europa (Zhang et al, 2020), e V. parahaemolyticus encontrado em regiões costeiras de clima temperado e tropical, com maior incidência em ambientes aquáticos salinos (Rosa et al, 2017).…”
Section: Vibrioses Na Carcinicultura E O Potencial Antimicrobiano Da ...unclassified